1988
DOI: 10.7589/0090-3558-24.4.627
|View full text |Cite
|
Sign up to set email alerts
|

An Epizootic of Mycoplasma Ovipneumoniae Infection in Captive Dall's Sheep (Ovis Dalli Dalli)

Abstract: In late spring of 1986, 10 of 23 Dall's sheep (Ovis dalli dalli) at the Metropolitan Toronto Zoo were moved to a new exhibit, where all developed severe respiratory signs refractory to anthelmintic and antibiotic therapy. In July, two animals died with chronic active bronch-pneumonia, and a third was euthanized because of pneumonia several months later. Bacteria were not isolated from the lungs of the first, steptococci and Pasteurella hemolytica were isolated from the other two, respectively; Mycoplasma ovipn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…In some other ovine species, M. ovipneumoniae has been associated with severe fatal pneumonia epidemics following contact with domestic sheep. The first report was given for captive Dall's sheep ( Ovis dalli ) in Canada [20] and more recently, M. ovipneumoniae was identified as a primary cause of pneumonia epidemics in free-ranging bighorn sheep ( Ovis canadensis ); a devastating disease that has been recognized in bighorn populations in North America for centuries [21][23].…”
Section: Discussionmentioning
confidence: 99%
“…In some other ovine species, M. ovipneumoniae has been associated with severe fatal pneumonia epidemics following contact with domestic sheep. The first report was given for captive Dall's sheep ( Ovis dalli ) in Canada [20] and more recently, M. ovipneumoniae was identified as a primary cause of pneumonia epidemics in free-ranging bighorn sheep ( Ovis canadensis ); a devastating disease that has been recognized in bighorn populations in North America for centuries [21][23].…”
Section: Discussionmentioning
confidence: 99%
“…In bighorn sheep populations outside of Hells Canyon, the association is at the population level based on serologic data obtained from adult bighorn sheep only. A previous study provided strong evidence of a role for M. ovipneumoniae in a pneumonia outbreak in a captive population of a closely related sheep species (Dall's sheep [Ovis dalli]), and the results of that study provided a valuable guide for this investigation (4).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect hemagglutination was performed as described elsewhere (4,8). Antigen was prepared using Mycoplasma ovipneumoniae strain 06OR03, grown in Mycoplasma broth (Hardy Diagnostics; 37°C, 5% CO 2 , 5 days).…”
Section: Methodsmentioning
confidence: 99%
“…11,16,102,103 Later studies have suggested that M. ovipneumoniae and Pasteurella hemolytica biotype A serotypes act synergistically to produce a chronic disease (atypical pneumonia) principally affecting lambs up to 12 months of age. 58 Mortality rarely exceeds 10%, 59 even under experimental conditions, but considerable economic loss due to unthriftiness can occur.…”
Section: Mycoplasma Ovipneumoniaementioning
confidence: 99%